A Review of Neurobehavioral Challenges in Children Exposed Prenatally to Intrauterine Opioid - Kamaledin Alaedini; Kaveh Haddadi; Leila Asadian (Mazandaran University of Medical Sciences, 2017)
Context: Substance abuse has remained a worldwide issue for many years and in recent decades there has been a major growth in the number of individuals consuming opioids. Several studies have discovered that young kids who have been exposed to opioids develop greater damages in overall intellectual capabilities and neurobehavioral functions than non-exposed children. Evidence Acquisition: The purpose of this study was to evaluate the surviving texts on the incidence of challenging behavior among kids due to prenatal medication contact. Overall, out of 84 identified manuscripts, 18 were established to consider intellectual, psychomotor, and behavior consequences in opioid-exposed infants, precollege and college children when matched with healthy no-opioid-exposed controls. Results: The results indicate that children exposed to opioid in utero may be cognitively affected over time, even once located in stable families on an actual early age. Somewhat, susceptibilities seem to rise by age for girls, and the unprotected boys persist behind non exposed boys entirely through infancy and into college age. Therefore, there looks to be a constant deleterious consequence of factors associated with prenatal medication contact over time. Conclusions: The results indicate children exposed to opioid in utero may be cognitively affected over time, even once located in stable families on an actual early age. The natural susceptibilities of prenatally drug-exposed children can affect initial intellectual skills which yet again are extremely associated with advanced mental capabilities. It is feasible that pre- and postnatal genetic susceptibilities and ecological issues cooperate in a transactional method through the child's lifespan.